Stare decisis and ratio decidendi - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2014)
The doctrine of stare decisis or the rule of judicial precedent dictates that it is necessary for each lower tier to accept loyally the decision of the higher tiers. Thus, a court other than the highest court is obliged generally to follow the decision ofthe court at a higher or the same level in the court structure subject to certain exceptions. The application of the doctrine from a higher court to a lower court is called the vertical stare decisis. Whereas, the notion that a judge is bound to follow or respect the decision of an earlier judge of similar or coordinate jurisdiction is called horizontal stare decisis. Further, the rule of judicial precedent shall apply whenever the relevant facts of an earlier case is similar to the facts of a subsequent case, ie., the relevant facts of the two cases are similar. However, if the facts are not similar then the earlier decision would be distinguished and as such would not be binding on the subsequent case. In light of the above, this chapter discusses the merits and demerits of this doctrine, the working of this doctrine with reference to its application in England and Malaysia, the powers of the Federal Court to review its own earlier decision, the definition of ratio decidendi and obiter dicta and its application.